Liquidity, credit risks & banks' size on profitability: pre-analysis of Malaysian commercial bank / Norliana Zaini and Rosshamira Arna Ismail - Zaini, Norliana; Ismail, Rosshamira Arna (Faculty of Business and Management, 2014)
These researches focus on the relationship between profitability with liquidity, credit risk and bank size of six local commercial banks in Malaysia consist of RHB Bank, Malayan Banking Berhad (Maybank), Alliance Bank Berhad, Public Bank, Affin Bank and Hong Leong Bank. The purpose of the research is to know the determinant of commercial bank’s profitability, whether liquidity, risk or size were influence in profitability or not. In addition, by doing this research the researchers will know whether there are any significant relationships between variables. This relationship can be test by descriptive analysis result from E-views application. These research been conducted by using secondary data from annual report consist of financial statement and financial ratio of these commercial banks from year 2004 until 2013. The researchers finding show that liquidity and bank size with profitability have positive relationship which is the increasing in liquidity and bank size will make profitability also increasing. On the other hand, the credit risk shows negative relationships with profitability prove that the decreasing in credit risk will make increasing in profitability.